Glass jaw : a manifesto for defending fragile reputations in an age of instant scandal - Dezenhall, Eric. (New York, NY : Twelve, 2014)
"In boxing terms, a tough-looking fighter who can't take a punch is said to have a "glass jaw," and so it is these days with targets of controversy. Down the rabbit hole of scandal, the weak are strong, the strong are weak. GLASS JAW is a manifesto for these times, written by crisis management warhorse Eric Dezenhall who has spent three decades inside of some of the most intense controversies in recent memory. In the digital age of 24/7 news, information is easily acquired and quickly spread, and this has changed the fundamental nature of controversy, rendering once mighty organizations and individuals powerless against scandal. Think Toyota, Susan G. Komen, Paula Deen, Tiger Woods, Penn State and Joe Paterno, BP, the Duke Lacrosse players, Lance Armstrong, Manti Te'o, and Anthony Weiner. Here Dezenhall defines this new reality where information moves at the speed of light and reputations are tarnished ever faster. In GLASS JAW, he analyzes controversy and scandal from the perspective of the truth-telling crisis management veteran to demystify the paper tiger "spin" industry, offering lessons learned, crucial corrective measures, and counterintuitive insights, such as: How there really is no getting ahead of a bad story The art of the public apology Why a crisis is not an opportunity and Hemingway's The Old man and the Sea is the I Ching of crisis management (because the old man survived and nothing more) The problem with "getting it all out there" and The Nixon Fallacy: if only he had just said "I screwed up," the whole thing would have gone away-not a chance Why you are the enemy: the self sabotage of technology, cameras, tweets, and emails "--
Machine generated contents note: SECTION I How Scandal Has Changed (and How It Hasn't) -- ch. 1 The Fiasco Vortex -- ch. 2 When Scandal Went to Sleep -- ch. 3 "Monetizing Humiliation" -- ch. 4 Brittle -- Why and How Goliath Became David (Part 1 -- The Syndrome) -- ch. 5 Brittle -- Why and How Goliath Became David (Part 2 -- The Mindset) -- ch. 6 Social Media Is the Problem, Rarely the Solution -- SECTION II Who Do You Think You're Spinning? -- ch. 7 The Eight Most Baseless Crisis Management Cliches -- ch. 8 The Three Apologies -- ch. 9 The "Spindustrial" Complex -- ch. 10 The Myth of Reputation Management (Whatever That Means) -- SECTION III The Physics of Controversy -- ch. 11 Controversy Shortcuts and Cascades -- ch. 12 The Ingredients of Scandal -- SECTION IV Redefining What It Means to Win -- ch. 13 The Controversy "Iceberg" -- ch. 14 Fewer Gurus, More Grown-ups.
Includes index.
Keywords: Public relations; Reputation; Public opinion; Crisis management; Corporate image; BUSINESS & ECONOMICS / Public Relations; PSYCHOLOGY / Applied Psychology; Corporate image; Crisis management; Public opinion; Public relations; Reputation